Historical relations between the arab gulf countries and Russia (International relations and international law Journal, 2020)
Russia began making contact with Gulf States back in 1932, when the USSR became one of thefirst countries that formally recognized Saudi Arabia and established diplomatic relations with the state.Shortly after, due to the change in the Soviets’ party line (conversion to a new ideology and developmentof a moderate stance towards regional conflicts), the relations were suspended. The aggravation ofinternational relations in the region was also the result of the competition between the Great Powers, andtheir respective political ambition. In the light of “West—East” political-military confrontation, the SovietUnion took immediate interest in the latest regional developments.This article used descriptive approach to the specificity of the problem of the study, which aims tostudy relations and differences, where this method is concerned with the study of what is the object andinterpretation and determine the relationships between the facts.The results of the study reached that Russia is one of the largest oil and gas producers in the world,and the largest oil exporter outside OPEC, as it usually seeks to maintain high energy prices despite tensionsand conflicts in the Middle East, as it has caused huge losses to the economy of the Gulf countriesdue to lower oil prices. The volume of trade exchange between Russia and the countries of the CooperationCouncil is very low compared to the Gulf’s trade relations with China. This may be due to the factthat Russia is futile in trade, although the latter is working to correct this deficit, but the desired resultsmay take some time.In the changing world, Moscow’s allies are not necessarily Washington’s foes, and vice versa. Cooperationbetween Russia and Gulf States is based on their shared interests, in particular, fighting internationalterrorism.Key words: Russia, Arabian Gulf, GCC, Syria, Saudi Arabia, UAE, international relations, oil.